Politik Hukum Pengaturan Right to Vote and Right to be Candidate dalam Undang-Undang Pasca Putusan Mahkamah Konstitusi - Rachman, Irfan Nur (Mahkamah Konstitusi Republik Indonesia, 2013)
The Constitutional Court in some award restored the right to vote (right to vote) and the right to choose (right to be candidate) for citizens. Some verdict related to the recovery of the political rights, namely the ruling Number 011-017/PUU-I/2003 on Return Political Rights For former members of the Illegal organization of the Communist Party of Indonesia and Other Illicit Organization and decision Number 102/PUU-VII/2009 on the use of ID card or passport in the elections. The ruling of the Constitutional Court have a legal binding force since spoken in plenary session. The nature of the ruling of the Constitutional Court are final and binding, it means there is no other remedy that can be reached by the parties and also the ruling of the Constitutional Court is not only binding on the parties but also binds all citizens of Indonesia (erga omnes). The ruling of the Constitutional Court was to be acted upon by the ruling of the Constitutional Court, addressad in this case is the President and DPR through a revision of the provisions that have been